1978
DOI: 10.1002/ana.410030311
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in presenile and senile dementia

Abstract: Forty-seven hospitalized patients with a diagnosis of presenile or senile dementia and without focal neurological disease of major systemic illness were given complete neurological, neuroradiological, and neuropsychological examinations. Mortality at one year after hospitalization was determined, 12 patients being lost to follow-up. Of the remaining 35 patients, 19 were alive and 1l had died. These groups did not differ in age, education, length of dementia history, sex, race, or degree of cerebral atrophy (by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…This result is consistent with the impairment of left-right orientation in AD patients that is observed on other tasks (Kaszniak et al, 1978), but fails to replicate the negative results of Brouwers et al (1984) who found no effect of dementia upon performance of the Standardized Road Map Test. Brouwers et al, using a somewhat younger group of subjects (mean age 59.7 vs. 70.9 in the present study) obtained a mean group difference similar to that observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This result is consistent with the impairment of left-right orientation in AD patients that is observed on other tasks (Kaszniak et al, 1978), but fails to replicate the negative results of Brouwers et al (1984) who found no effect of dementia upon performance of the Standardized Road Map Test. Brouwers et al, using a somewhat younger group of subjects (mean age 59.7 vs. 70.9 in the present study) obtained a mean group difference similar to that observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…It seems surprising that mental-rotation ability should be unimpaired in these patients despite the presence of visuoconstructional and visuoperceptual deficits. Furthermore, left-right discrimination (pointing to lateralized body parts) has been reported to be impaired in AD patients and to decline further in more advanced cases (Kaszniak et al, 1978), while it is unimpaired in 70-year-old normals (Borod, Goodglass, & Kaplan, 1980). The present study is an investigation into the cognitive basis of spatial disorientation in AD.…”
mentioning
confidence: 76%
“…Survival rates have varied by severity of impairment, age, sex, and comorbidity. [19][20][21][22][23][24] The few studies of elderly nonde- Because men and women in this sample differed by marital status and other health and social characteristics, we entered interaction terms for sex and key independent variables in the multivariate models. However, high correlations between these variables and the interaction terms-for example, .59 (age), .76 (problems in daily living), .75 (self-assessed health), and .85 (social support)-precluded their inclusion in the model.…”
Section: Introductionmentioning
confidence: 99%
“…(Helm-Estabrooks 1992), WAB = Western Aphasia Buttety (Kertesz 1982 improvements of targeted language functions : McNeil and colleagues reported improved word-finding with a behavioural plus pharmacological treatment and Schneider and colleagues reported improved production of simple sentence structure with a verbal plus gestural treatment. Whereas both studies documented treatment effectiveness and short-term maintenance, both patients, as expected with PPA, eventually showed decline of target language behaviours.…”
Section: Mtdda = Minnesota Test For Drfferentiaf Diagnosis Ofmentioning
confidence: 96%
“…Treatment 3 (January 1996 to present) Following BDB training in December 1995, D. D.'s communication skills were reevaluated, Findings from the ADP (Helm-Estabrooks and Albert 1991) and the WAB (Kertesz 1982) indicated that her language skills in all modalities showed little change compared to findings from her September 1995 evaluation (see table 1). At this time, in depth assessment of her verbal expression skills was also completed in an attempt to differentiate motor speech deficits from expressive language deficits.…”
Section: L Murraymentioning
confidence: 98%